Praktická výuka endoskopických metod v Edukacním centru pro anatomii a endoskopii Anatomického ústavu 3. lékarské fakulty Univerzity Karlovy v Praze--lze zajít jeste dále? - Doubková, A; Smrzová, T (Casopis lekaru ceskych, 2008)
Unique multimedial centre for education in endoscopic surgery and miniinvasive surgery was established at the Department of Anatomy of Third Medical Faculty of Charles University in Prague during 2000 to 2005. A new fixation method was introduced to enable the repeated usage of cadavers for imitation of surgical interventions. One operating theatre was equipped with an audio-video network and a wireless connection to internet together with a graphic studio for the production of our own educational materials. The Centre's web side enables e-learning study. At the dissection courses for medical students arthroscopies of small and large joints, laparoscopies, bronchoscopies and gastroscopies are demonstrated. Also postgradual education courses for physicians are organised. They bring a great opportunity to gain experience in endoscopic surgery and miniinvasive surgery on specifically embalmed anatomical material.
Keywords: studium lékařství pregraduální; vyučování; Education, Graduate; Cadaver; Teaching; endoskopie; Humans; Endoscopy; lidé; studium vysokoškolské; mrtvola; Education, Medical, Undergraduate